A clinical and epidemiological study of non-venereal genital dermatoses: A cross-sectional, hospital-based study from Nepal - Vikash Paudel; Deepa Chudal; Upama Paudel; Dwarika Prasad Shrestha (Our Dermatology Online, 2022)
Background: Non-venereal genital dermatoses are the conditions of the genitalia that are not transmitted sexually. They may be confused with venereal diseases and be responsible for concerns among patients as well as diagnostic dilemmas for physicians. This study was conducted to determine the prevalence and describe the patterns of non-venereal genital conditions. Methods: This was a hospital-based, cross-sectional, prospective study conducted in a tertiary center in Kathmandu, Nepal, over a period of one year. Non-probability purposive sampling was employed to select the samples. Two hundred patients were enrolled in the study. Ethical approval was taken prior to the study. Detailed history taking along with a complete cutaneous examination were conducted for all patients and recorded in a preformed proforma. Results: Among 21366 patients, two hundred patients had non-venereal genital dermatoses. The prevalence of non-venereal dermatoses was 0.93 %. The mean age of the patient was 29.5 ± 15 years, ranging from 2 months to 81 years. The male-to-female ratio was 2.7:1. Itching was the most common presentation (46%). Fifty-four different types of non-venereal diseases were encountered and classified into inflammatory lesions (n = 84; 42%), infections and infestations (n = 43; 21.5%), normal variants and benign abnormalities (n = 41; 20.5%), and miscellaneous (n = 21; 10.5%). The most common were, among inflammatory dermatoses, drug reactions (11.5%) and eczema (6.5%) and, among infections and infestations, scabies (9.5%) and fungal infections (7.5%). Conclusion: Non-venereal genital dermatoses are important yet less common dermatological conditions. A number of patients have misconceptions about them as venereal. A comprehensive study of non-venereal dermatological genital conditions is required for careful management to minimize morbidity.